POLA PENGASUHAN ORANGTUA DALAM PENGGUNAAN GADGET BAGI ANAK USIA 4-6 TAHUN DI DUSUN 3 DESA BOKASAPE TIMUR KECAMATAN WOLOWARU KABUPATEN ENDE - Ecalia Nesta, Klara; Novyani Seran, Theodorina; Kale, Sartika; Syukur, Abdul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Parenting plays a crucial role in early childhood development. In the digital era, parenting also involves regulating children’s gadget use. Inappropriate gadget use can negatively affect children’s development, thus necessitating parental supervision and guidance. This study aims to describe parenting patterns in gadget use among children aged 4-6 years in Dusun 3, Bokasape Timur Village, Wolowaru District, Ende Regency. The research employs a qualitative approach with a descriptive method. Data were collected through in-depth interviews, and their validity was ensured using source triangulation. Data analysis followed the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing. The findings reveal three parenting styles applied: democratic, authoritarian, and permissive. Authoritarian parents tend to impose strict rules on gadget use, whereas permissive parents grant excessive freedom with minimal supervision. In contrast, democratic parents balance rules with children’s needs by providing guidance and selecting educational content. Each parenting style has its own strengths and limitations; therefore, the application of parenting in managing gadget use should be adapted to the child’s characteristics.